Municipal councils and central authority in Mauretania Caesariensis And Tingitana: a study in The mechanisms of self-government and Roman domination - Mohamed SENOUCI (Teacher Training College of Bouzareah, 2025)
Abstract: The objective of this study is to define the complex relationship between municipal councils (curiae) and the provincial governor in Roman Mauretania (Caesariensis and Tingitana). It specifically aims to assess the balance of power between local self-government and centralized Roman authority. The study adopts a historical-analytical methodology, based on a critical examination of primary sources. The core evidence is drawn from epigraphic material (honorific and administrative inscriptions) and relevant archaeological findings, which are interpreted to reconstruct the councils' functions and the governor's oversight mechanisms. The findings indicate that while municipal councils possessed significant *de facto* autonomy in daily administrative, financial, and judicial matters—often funded through the system of Euergetism—their authority was ultimately circumscribed by the governor's supervisory role. This intervention was most prominent in major financial projects, capital judicial cases, and matters of imperial interest. The study concludes that the relationship was not one of simple domination but a structured balance, representing a system of controlled autonomy that served both local civic pride and Roman imperial stability.
المجالس البلدية والسلطة المركزية في موريطانيا القيصرية و الطنجية: دراسة في آليات الحكم الذاتي و الهيمنة الرومانية
Keywords: Mauretania Caesariensis; Mauretania Tingitana; Roman Administration